The environmental impact of small-bowel capsule endoscopy - Pioche, Mathieu; Cunha Neves, Joao A.; Pohl, Heiko; Lê, Minh-Quyen; Grau, Raphaelle; Dray, Xavier; Yzet, Clara; Mochet, Mikael; Jacques, Jérémie; Wallenhorst, Timothée; Rivory, Jérôme; Siret, Nadège; Peillet, Anne-Laure; Chevaux, Jean-Baptiste; Mion, François; Chaput, Ulriikka; Jacob, Philippe; Grinberg, Daniel; Saurin, Jean-Christophe; Baddeley, Robin; Rodriguez de Santiago, Enrique; Cottinet, Pierre-Jean; and the Sustainability Committee of the French Endoscopy Society (SFED) (Endoscopy, 2024)
Introduction The environmental impact of endoscopy, including small-bowel capsule endoscopy (SBCE), is a topic of growing attention and concern. This study aimed to evaluate the greenhouse gas (GHG) emissions (kgCO2) generated by an SBCE procedure.Methods Life cycle assessment methodology (ISO 14040) was used to evaluate three brands of SBCE device and included emissions generated by patient travel, bowel preparation, capsule examination, and video recording. A survey of 87 physicians and 120 patients was conducted to obtain data on travel, activities undertaken during the procedure, and awareness of environmental impacts.Results The capsule itself (4 g) accounted for < 6 % of the total product weight. Packaging (43–119 g) accounted for 9 %–97 % of total weight, and included deactivation magnets (5 g [4 %–6 %]) and paper instructions (11–50 g [up to 40 %]). A full SBCE procedure generated approximately 20 kgCO2, with 0.04 kgCO2 (0.2 %) attributable to the capsule itself and 18 kgCO2 (94.7 %) generated by patient travel. Capsule retrieval using a dedicated device would add 0.98 kgCO2 to the carbon footprint. Capsule deconstruction revealed materials (e. g. neodymium) that are prohibited from environmental disposal; 76 % of patients were not aware of the illegal nature of capsule disposal via wastewater, and 63 % would have been willing to retrieve it. The carbon impact of data storage and capsule reading was negligible.Conclusion The carbon footprint of SBCE is mainly determined by patient travel. The capsule device itself has a relatively low carbon footprint. Given that disposal of capsule components via wastewater is illegal, retrieval of the capsule is necessary but would likely be associated with an increase in device-related emissions.